Technical alterations during an incremental field test in elite male tennis players - Brechbuhl, C.; Girard, O.; Millet, G. P.; Schmitt, L. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: We investigated technical and physiological responses along with their relationships during an incremental field test to exhaustion specific to tennis (TEST) in elite players.